A Frequency‐Selective pH‐Responsive paraCEST Agent. Issue 48 (6th October 2020) - Ratnakar, S. James; Chirayil, Sara; Funk, Alexander M.; Zhang, Shanrong; Queiró, João F.; Geraldes, Carlos F. G. C.; Kovacs, Zoltan; Sherry, A. Dean
Abstract: Paramagnetic chemical exchange saturation transfer (paraCEST) agents are well‐suited for imaging tissue pH because the basis of CEST, chemical exchange, is inherently sensitive to pH. Several previous pH‐sensitive paraCEST agents were based on an exchanging Ln 3+ ‐bound water molecule as the CEST antenna but this design often added additional line‐broadening to the bulk water signal due to T 2 exchange. We report herein a pH‐sensitive paraCEST agent that lacks an inner‐sphere water molecule but contains one Ln‐bound −OH group for CEST activation. The Yb 3+ complex, Yb(1 ), displayed a single, highly shifted CEST peak originating from the exchangeable Yb‐OH proton, the frequency of which changed over the biologically relevant pH range. CEST images of phantoms ranging in pH from 6 to 8 demonstrate the potential of this agent for imaging pH. Initial rodent imaging studies showed that Gd(1 ) remains in the vascular system much longer than anticipated but is cleared slowly via renal filtration. Abstract : The Yb 3+ complex of 10‐(2‐hydroxypropyl)‐1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7‐tris‐(methylenephosphonic acid) displays a single highly shifted CEST peak arising from the Ln 3+ ‐coordinated exchangeable −OH proton, which appears well outside the typical tissue magnetization transfer (MT) window. The frequency of the CEST peak shows a large chemical shift dispersion over the physiological pH range.